PERILAKU PEMILIH PEMULA PADA PEMILIHAN BUPATI DAN WAKIL BUPATI KABUPATEN POLEWALI MANDAR PROVINSI SULAWESI BARAT PERIODE 2019-2024 - Rustan IR; Munawir Ariffin (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2019)
This research aims to (1) Describe and analyze the Behavior of Beginner Voters in the Election of Regent and Deputy Regent of Polewali Mandar in 2019-2024, (2) Describe and analyze the tendency of novice voter behavior in dropping their choices to certain candidates or candidates in the election of Regent and Deputy Regent Polewali Mandar. This type of research is a qualitative descriptive study. The results showed that novice voters in Campalagian Subdistrict in the election of the Regent and Deputy Regent in 2019 in Polewali Mandar Regency, namely: (1) Rational voters almost the majority of the community considered the vision and mission offered by the candidate pair, (2) Factors affecting voters are influenced by three aspects namely the sociological, psychological and rational approaches, namely the figure/idol of the candidate pair, the vision and mission offered, the supporting party, the candidate's background, the candidate's education, and the supporting party.